The effect of an exercise intervention on insulin sensitivity, insulin secretion and insulin clearance in black obese South African women - Fortuin-De Smidt, Melony (Department of Human Biology, 2021)
Introduction: Black African populations present with low insulin sensitivity (SI) and hyperinsulinemia, the latter due to high insulin secretion and reduced clearance. In addition, they exhibit lower levels of central and ectopic fat, compared to their white counterparts, contradicting the known correlates of SI typically reported in white populations. Moreover, in black African women hyperinsulinemia is in excess of the level needed to compensate for low SI, with a corresponding high disposition index (DI), a marker of insulin response that accounts for the level of SI. Further, obese, black African women have a high risk for type 2 diabetes (T2D), but the correlates of hyperinsulinemia have not been fully elucidated, especially the role of ectopic fat and body fat distribution. Exercise training is beneficial to improve SI and DI, however, whether these effects are mediated by changes in ectopic fat in skeletal muscle, liver and pancreatic depots is unknown. Accordingly, exercise training can be used as a model to assess the correlates of hyperinsulinemia and SI in cohorts at high risk for developing T2D, such as obese black African women. This thesis therefore aims to describe the correlates of hyperinsulinemia and SI and to evaluate the effect of exercise training on these components with emphasis on the role of body fat distribution and ectopic fat in mediating these changes. Methods: Firstly, a cross-sectional analysis of 45 obese (BMI 30-40 kg/m2 ) black South African women (age 20-35 years) without T2D was conducted. Thereafter the women were block randomized into an exercise training (n=23) or no exercise (control, n=22) group. The exercise training group participated in a 12-week combined aerobic and resistance training programme (40-60 min session, 4 days/week) supervised by a biokineticist. Pre and post-intervention testing included assessment of acute insulin response to glucose (AIRg), SI, DI (AIRg x SI), insulin secretion rate (ISR), hepatic insulin extraction (HIE) and peripheral insulin clearance (CLp) (frequently sampled intravenous glucose tolerance test); body fat mass and regional adiposity (dual-energy X-ray absorptiometry); hepatic, pancreatic and skeletal muscle fat and abdominal subcutaneous (aSAT) and visceral adipose tissue (VAT) (magnetic resonance imaging); intramyocellular (IMCL) and extramyocellular fat content (EMCL) (magnetic resonance spectroscopy). Results: The baseline results showed that a high DI was associated with low VAT (r0.565, p< 0.001), pancreatic fat, soleus IMCL and EMCL with VAT explaining most of the variance in DI (32%). SI was inversely associated with VAT (rho -0.417, p=0.007) and AIRg was inversely and HIE was positively associated with VAT-aSAT ratio (rho - 0.345, p=0.029 and rho 0.510, p=0.011, respectively). DI was positively associated with CLp (rho 0.528, p=0.006), while its components (SI and AIRg) were not. Results from the intervention showed that exercise training increased DI (median (interquartile range): 6.1 (3.6-7.1) to 6.5 (5.6-9.2) x103 arbitrary units, p=0.028), SI (2.0 (1.2-2.8) to 2.2 (1.5-3.7) (mU/l) -1 min -1 , p=0.005) and VO2peak (mean ± standard deviation: 24.9±2.42 to 27.6±3.39 ml/kg/min, p< 0.001), with no changes in control group. Exercise training decreased body weight (84.1±8.7 to 83.3±.9.7 kg, p=0.038) and gynoid fat mass (18.5±1.7 to 18.2±1.6%, p< 0.001). AIRg, ISR, HIE, CLp, aSAT, VAT and ectopic fat were unchanged after exercise training. However, the control group increased body weight and aSAT. The increase in SI and DI were not associated with changes in body composition, body fat distribution or ectopic fat. Conclusion: Novel results from our cross-sectional analysis showed that, in obese black South African women, DI was positively associated with peripheral insulin clearance, probably due to higher SI of peripheral tissue. Moreover, the most important correlate of a high DI was low VAT independent of ectopic fat accumulation in other sites. Further, we showed that low AIRg and high HIE correlated with a high VAT-aSAT ratio, while low SI was associated with high VAT. These associations require further exploration to determine direction of causality. Findings from our exercise intervention study extend on previous research by showing that moderate-to-high intensity combined aerobic and resistance exercise training increased SI and improved cardiovascular fitness, but insulin secretion, hepatic insulin clearance, ectopic and central fat depots did not change. Our results suggest that hyperinsulinemia may not occur solely as a compensatory mechanism for low SI and that ectopic and central fat might not be the primary correlates of insulin resistance in this cohort. Rather, intrinsic factors within muscle and adipose tissue may be putative mediators for observed improvements in the metabolic outcomes but will require further elucidation. Further research is required to confirm the causal role of VAT on low DI and to determine whether a long-term exercise training program and/or a low carbohydrate/glycemic index diet will reduce AIRg in those with hyperinsulinemia.